2010
DOI: 10.1159/000258710
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Agents Involved in Septic Miscarriage

Abstract: Even though the understanding of the cause of early pregnancy loss due to chromosomal abnormalities has improved, there is a dearth of knowledge of the causes of loss in euploid conceptuses. Maternal infections are a cause of abort in humans, but the mechanisms are not clear, so we have developed a murine model to study the mechanism of septic abortion by inducing embryonic resorption (ER) with lipopolysaccharide (LPS). We demonstrated that augmented production of nitric oxide (NO) and prostaglandins (PG) is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…COXderived lipid mediators such as PGE 2 or PGF 2 ␣ have been shown to be significantly increased following infections [218][219][220] or inflammations, especially during pregnancy [221][222][223] . Several clinical studies and case reports have shown possible contributions of viral infections and abnormal immune response in some cases of autism [224] .…”
Section: Involvement Of Immunological Factorsmentioning
confidence: 99%
“…COXderived lipid mediators such as PGE 2 or PGF 2 ␣ have been shown to be significantly increased following infections [218][219][220] or inflammations, especially during pregnancy [221][222][223] . Several clinical studies and case reports have shown possible contributions of viral infections and abnormal immune response in some cases of autism [224] .…”
Section: Involvement Of Immunological Factorsmentioning
confidence: 99%
“…[3] These results are consistent with the results of earlier meta-analyses. [4, 5] The biological mechanism explaining how smoking might lead to miscarriage remains unclear,[1] but hypotheses include fetal hypoxia and changes in placental vasculature,[69] inflammation [1014] and immune modulation. [13, 15]…”
Section: Introductionmentioning
confidence: 99%
“…The reproductive performance was examined because it was reported that prenatal LPS induces spontaneous abortions (Aisemberg et al, 2010;Lee et al, 2013b;Xu et al, 2013) and intrauterine fetal death or embryonic resorption (Paintlia et al, 2008;Xu et al, 2006;Zhao et al, 2008). Since environmental information received by a mother can induce a phenotype change in her offspring, commonly known as a maternal effect (trans-generational effect), the maternal behavior was assessed Soto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%